The Data Extraction and Longitudinal Trend Analysis Network Study of Distributed Automated Postmarket Cardiovascular Device Safety Surveillance. (January 2015) - Kumar, Amit; Matheny, Michael E.; Ho, Kalon K.L.; Yeh, Robert W.; Piemonte, Thomas C.; Waldman, Howard; Shah, Pinak B.; Cope, Richard; Normand, Sharon-Lise T.; Donnelly, Sharon; Robbins, Susan; Resnic, Frederic S.
<x xml:space="preserve">Abstract</x> Background— Current approaches for postmarket medical device safety surveillance are limited in their ability to produce timely and accurate assessments of adverse event rates. Methods and Results— The Data Extraction and Longitudinal Trend Analysis (DELTA) network study was a multicenter prospective observational study designed to evaluate the safety of devices used during percutaneous coronary interventions. All adult patients undergoing percutaneous coronary intervention from January 2008 to December 2012 at 5 participating Massachusetts sites were included. A safety alert was triggered if the cumulative observed adverse event rates for the study device exceeded the upper 95% confidence interval of the event rates of propensity-matched control cohort. Prespecified sensitivity analyses were developed to validate any identified safety signal. A total of 23 805 consecutive percutaneous coronary intervention procedures were evaluated. Two of 24 safety analyses triggered safety alerts. Patients receiving Perclose vascular closure device experienced an increased risk of minor vascular complications (relative risk, 4.14; P<0.01) and any vascular complication (relative risk, 2.06; P=0.01) when compared with propensity-matched patients receiving alternative vascular closure device, a result primarily driven by relatively high event rates at 1 participating center. Sensitivity analyses based on alternative risk adjustment methods confirmed a pattern of increased rate of complications at 1 of the 5 participating sites in their use of Perclose vascular closure device. Conclusions— The DELTA network study demonstrates that distributed automated prospective safety surveillance has the potential of providing near real-time assessment of safety risks of newly approved medical devices.